Lagolândia — paisagens de festa e de fé: uma comunidade percebida pelas festividades - Curado, João Guilherme da Trindade (2011)
In this paper we investigate the landscape of parties and faith of a small community that inhabits Lagolândia, Pirenópolis district, which arose in the early twentieth century due to the construction of a church in devotion to Our Lady Imaculada Conceição, and, each party to the patron, the agglomeration is amplified as well as parties who were implanted there. Due to the representativeness of the festivities for this community, we prepared a festive Lagolândia cycle, with four events, the greater involvement that they have with lagolandenses: Feast of Our Lady Imaculada Conceição, Folia de Reis, Folia Feast of St. João and Divino Pai Eterno. The local "festive time" expands to other numerous honors devotional, which collaborates with our assertion that such a community may be perceived by the parties. To this end, we compiled a rescue of the historicity of the domains of religion through planting churches and chapels by goianas landscapes, as well as the system of "donation" of land that allowed the occupation and therefore also the genesis of the town in Goiás. Some reports from European travelers are the first documented mentions of the landscape and local parties, therefore, were mentioned. Then, the four parties of the festive cycle are presented for, soon after, being addressed as rituals, so that the memory and perceptions related to corroborate the tradition understanding of the meanings of the party for that community located on Rio do Peixe shores. The landscapes of parties and their contexts are studied by means of photographs, and old images contributed also to the analysis of the landscape of the past festivals. In each cycle of festivities, which encompass the temporal dimension of one year, several possibilities were discussed that contribute to the exercise of perception of landscapes in order to explain a little more about a community by the party and the faith.